Cover Picture: Diversified exploitation of aerolysin nanopore in single‐molecule sensing and protein sequencing (View 4/2020). Issue 4 (2nd December 2020) - Lu, Si‐Min; Wu, Xue‐Yuan; Li, Meng‐Yin; Ying, Yi‐Lun; Long, Yi‐Tao
Abstract : In article number 20200006, Yi‐Tao Long, Yi‐Lun Ying and co‐workers display that aerolysin single‐biomolecule interface is developed to achieve single molecule sensing in a label free manner. To further enhance the sensing performance, sensing regions of Aerolysin nanopore are first determined by the combination of nanopore experiments and molecular dynamics simulation. Aerolysin sensing interface is subsequently designed and tailored at the precision of chemical group via site‐directed mutagenesis. After the well‐designed mutagenesis, electrochemically confined mutant Aerolysin nanopore shows the extremely high selectivity and sensitivity toward target single biomolecules, being further expecting to be widely applied in fast disease diagnosis and protein sequencing.